Investigating Difficulties that EFL Students Face in English Pronunciation in Secondary Schools in Ghat-Libya (Abhat Journal, 2024)
The current study was designed to investigate the pronunciation issues encountered by foreign language learners in Ghat, south-west Libya. The findings have important implications for understanding students' English pronunciation problems. This study employs qualitative research methods to acquire an extensive understanding of a topic. This study used two data collection tools: observation and a pronunciation test. During the observation, the initial ideas and perceptions were documented, and the verbal data was collected for further analysis. The data were gathered from three secondary schools in Ghat that teach English as a foreign language in approximately four lessons per week. The test consisted of ten sentences and was administered to five secondary school students. According to the study, the most common pronunciation challenges among EFL students are a) vowel sound confusion, b) consonant sound confusion, and c) inflectional morpheme errors. Students commonly use the sound /ɪ/ for front vowels and the sound /ɒ/ for back-rounded vowels and fail to pronounce central vowels due to problems in predicting pronunciation. Additionally, the survey found that the most prevalent consonant issues are p, f, v, ð, θ, z, ʃ, and ʧ. Finally, students frequently pronounce /s/ at the end of regular plural nouns; insert /ɪ/ before /s/ or /z/ in plural nouns, and before /d/ in past verbs, regardless of the preceding phonemes. Consequently, the researchers concluded that EFL students in Ghat secondary schools frequently pronounce the alphabet letter as written, failing to predict its pronunciation when the letter has numerous pronunciations.
Keywords: English pronunciation; EFL learners; vowel sounds; consonant sounds; inflectional morphemes.